1982
DOI: 10.1002/j.2050-0416.1982.tb04080.x
|View full text |Cite
|
Sign up to set email alerts
|

Esterases of Baker's Yeast. Iii. The Ester/Acid Ratio in Model Solutions

Abstract: Ester/acid equilibria were studied in reaction mixtures containing ethyl alcohol, ethyl caprylate or oaprylic acid, and baker's yeast or an esterase purified from baker's yeast in buffer. The equi librium concentration of ethyl caprylate after an incubation of yeast or a yeast esterase preparation with caprylic acid was the same as in the case where yeast or esterase preparation was incubated with the ethyl caprylate. The equilibrium attained depends not only on the concentration of the ester and the alcohol b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…As esterases are responsible for the breakdown of esters, it is clear that their activity may affect the concentration of certain volatile esters. In S. cerevisiae, for example, it has been shown that the balance between ester-synthesizing enzymes and esterases, such as Iah1p (also known as Est2p), is important for the net rate of ester accumulation (27)(28)(29)(30) (59,60,61,62,70). This indicates that esterases may also play a role in the formation of certain esters (42,62,70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As esterases are responsible for the breakdown of esters, it is clear that their activity may affect the concentration of certain volatile esters. In S. cerevisiae, for example, it has been shown that the balance between ester-synthesizing enzymes and esterases, such as Iah1p (also known as Est2p), is important for the net rate of ester accumulation (27)(28)(29)(30) (59,60,61,62,70). This indicates that esterases may also play a role in the formation of certain esters (42,62,70).…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, for example, it has been shown that the balance between ester-synthesizing enzymes and esterases, such as Iah1p (also known as Est2p), is important for the net rate of ester accumulation (27)(28)(29)(30) (59,60,61,62,70). This indicates that esterases may also play a role in the formation of certain esters (42,62,70). In Acetobacter pasteurianus, for example, deletion of the esterase-encoding gene est1 causes the abolishment of ethyl acetate and isoamyl acetate production (15,36,37,50).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic analysis of esterases is one of the easiest ways to analyse enzyme variants, providing valuable information in the study of species differentiation, population structure and evolutionary relationships 5 . Yeast esterases are of particular interest because their activity can affect the flavour of various beverages and foods 9,11,3 . By regulating the equilibrium between esters and free acids, yeast esterases might determine ester synthesis, but seem to be mainly involved in their breakdown 6 .…”
mentioning
confidence: 99%
“…A technological aspect of great importance concerns the involvement of esterase activity in the formation of specific flavors in alcoholic beverages [1]. To detect esterase activity, some authors apply zymogram techniques by using such different substrates like 2-naphthyl acetate (2-NA) or p-nitrophenyl acetate (pNPA) and diazonium salts as coupling agents [2,3].…”
mentioning
confidence: 99%
“…Since esterase activity of yeasts, though rather low, can have a great influence in determining the aromatic profile of a given wine [1,3], the method was developed in order to detect the presence of esterase isoforms in oenological yeast strains. The yeast strain BR96 was obtained from the collection of the Istituto per l'Enologia of Asti (Italy).…”
mentioning
confidence: 99%